(untitled) (Revista Brasileira de Plantas Medicinais, 2000)
This work evaluated the in vitro growth and development of ginger explants submitted to different levels of NAA (0 - 0.25 - 0.5 - 0.75 - 1.0 mg/L) or BAP (0 - 0.5 -1.0- 1.5 - 2.0 mg/L) in solid and liquid medium, followed by the growth in the best combination of these growth regulators (0 and 0.5 mg/L NAA plus 0 and 1.0 mg/L BAP). NAA increased the shoots length in both solid and liquid medium. Maximum effect of NAA on the number and length of roots was achieved at concentration of 0.5 mg/L. BAP effected significantly the number of shoots in both media, with maximum response at 1.0 mg/L. In liquid medium the absence of BAP induced higher number of shoots and the length of shoots was affected by NAA and BAP, with best effects at 1.0 mg/L BAP, 0.5 mg/L and control. Root number and length were enhanced in liquid medium regardless the growth regulator treatment.